2005
DOI: 10.1097/01.don.0000153842.06657.e2
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility In Vitro Tests of Mineral Trioxide Aggregate and Regular and White Portland Cements

Abstract: Mineral trioxide aggregate (MTA) and Portland cement are being used in dentistry as root end-filling materials. However, biocompatibility data concerning genotoxicity and cytotoxicity are needed for complete risk assessment of these compounds. In the present study, genotoxic and cytotoxic effects of MTA and Portland cements were evaluated in vitro using the alkaline single cell gel (comet) assay and trypan blue exclusion test, respectively, on mouse lymphoma cells. The results demonstrated that the single cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
69
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 36 publications
4
69
0
6
Order By: Relevance
“…Portland cement has been proven to be biocompatible through previous studies that showed cements are not genotoxins [17][18][19][20]. The main component in cement, namely tricalcium silicate (C3S), has been shown to induce cell proliferation and HAP deposition on its surface [21].…”
Section: Introductionmentioning
confidence: 99%
“…Portland cement has been proven to be biocompatible through previous studies that showed cements are not genotoxins [17][18][19][20]. The main component in cement, namely tricalcium silicate (C3S), has been shown to induce cell proliferation and HAP deposition on its surface [21].…”
Section: Introductionmentioning
confidence: 99%
“…Portland cement (PC) has emerged as an alternative to MTA because of its relative lower cost, similar chemical composition and biocompatibility with MTA, and several studies have compared both materials (12)(13)(14)(15)(16). As PC may potentially be used as an endodontic material (11,17), it does not have sufficient radiopacity to be visualized radiographically, and therefore a radiopacifying agent must be added to it (11).…”
Section: Introductionmentioning
confidence: 99%
“…A range of calcium silicate based materials are currently being investigated for their potential use in dental and bone-contact applications [11][12][13][14] . Previous research 15 has demonstrated the in vitro bioactivity of the calcium sulphate hemihydrate-tricalcium silicate composite bone cement.…”
Section: Introductionmentioning
confidence: 99%